Adaptive finite time congestion tracking control for TCP/AQM system with input-saturation. Issue 2 (25th January 2022) - Shen, Jindong; Jing, Yuanwei; Ren, Tao
Abstract : In this paper, the finite time tracking control issue of the TCP/AQM system with input saturation and non-response flows such as UDP is studied. A novel AQM control algorithm is proposed by combining finite time control, prescribed performance control and fuzzy logic system. In order to obtain better disturbance suppression performance, the fuzzy logic system is adopted to deal with the external disturbance and the error disturbance generated by approximate input saturation function. The controller is designed to ensure that the queue tracking error converges to a specific region and achieve the practical finite time stability of all signals in the closed-loop system. The simulation results demonstrate the feasibility and superiority of the proposed method.